Chemical tools to monitor bladder cancer progression. (18th August 2022) - Gruba, Natalia; Stachurski, Lech; Lesner, Adam
Abstract: Background: Bladder cancer (BCa) is the most common cancer of the urinary system. Due to its high incidence and recurrence, as well as limited progress in the effective treatment, BCa is a challenge for today's medicine. Materials and Methods: We used a set of chromogenic substrates to differentiate between the stages of bladder cancer progression (G1 ( n  = 10), G2 ( n  = 10), G3 ( n  = 10)). The proteolytic activity in individual the urine samples was determined by absorbance measurements. Then inhibitors of particular classes of enzymes were used to determine which enzymes dominate at a given stage of the neoplastic disease. Results: The specific activity of enzymes in the urine of patients with confirmed bladder cancer was determined separately for three (G1, G2, G3) stages of the disease development. What is more, no activity was observed in urine of healthy people ( n  = 10). Discussion: Research shows that specific enzymes are associated with the development of specific stages of cancer. We suspect that the differences in the proteolytic activity of urine samples are due to the presence of a different set of enzymes that are directly related to the particular stage of the disease. Conclusion: We obtained three substrates for monitoring individual stages of bladder cancer development.